The Phenomenon of Using Face Filters in Finding Partners on Social Media - Lubis, Bella Yulisda; Sazali, Hasan (Journal Analytica Islamica, 2025)
The use of face filters on social media has become part of a self-presentation strategy, especially in the context of finding a partner. This study investigates the motives, perceptions and impact of women’s use of face filters in building online relationships. The method used is a qualitative approach with in-depth interview techniques with four informants, consisting of two unmarried women and two widows. The results of the study indicate that the reasons for using filters are related to the desire to appear more attractive, to increase self-confidence and as a form of self-expression. The informants’ perceptions of filters are divided into two views: as a form of manipulation and as a way to show the best version of themselves. In addition, it was found that unmarried women showed a greater tendency to rely on filters than widows.